1979
DOI: 10.1029/wr015i006p01633
|View full text |Cite
|
Sign up to set email alerts
|

Estimating soil water retention characteristics from particle size distribution, organic matter percent, and bulk density

Abstract: Regression models are presented for estimating soil-water-retention curves from particle-size distribution, percentage of organic matter, and bulk density. Models were developed from the measured soil-water-retention curves of artificially packed cores (7.6 x 7.6 cm) of 43 soil materials. These soil materials included 13 agricultural soils. Curves predicted with these models approximated reasonably well the measured water retention of 61 Missouri soils. Because conventional methods of obtaining retention curve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
395
1
27

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 699 publications
(433 citation statements)
references
References 9 publications
10
395
1
27
Order By: Relevance
“…Os resultados de Rawls et al (1991) mostram que, em elevados Ψ, a curva de retenção é influenciada por poros estruturais associados ao efeito da matéria orgânica na formação e na estabilidade da estrutura do solo. Em baixo Ψ, a composição granulométrica e a mineralogia do solo tornam-se mais importantes devido à superfície disponível para a adsorção de água (Gupta & Larson, 1979). Dessa forma, a curva de retenção de água permite relações de dependência entre os coeficientes das equações matemáticas que a descrevem com diferentes propriedades do solo, como o teor de argila, o teor de C orgânico, a área superficial específica e a densidade do solo (van den Berg et al, 1997).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Os resultados de Rawls et al (1991) mostram que, em elevados Ψ, a curva de retenção é influenciada por poros estruturais associados ao efeito da matéria orgânica na formação e na estabilidade da estrutura do solo. Em baixo Ψ, a composição granulométrica e a mineralogia do solo tornam-se mais importantes devido à superfície disponível para a adsorção de água (Gupta & Larson, 1979). Dessa forma, a curva de retenção de água permite relações de dependência entre os coeficientes das equações matemáticas que a descrevem com diferentes propriedades do solo, como o teor de argila, o teor de C orgânico, a área superficial específica e a densidade do solo (van den Berg et al, 1997).…”
Section: Introductionunclassified
“…Correlações de Pearson entre propriedades físicas do solo e os coeficientes de equações descritivas da curva de retenção de água do solo foram realizadas por Gupta & Larson (1979), Rawls et al (1991Rawls et al ( , 2003, van den Berg et al (1997) e Rasiah & Aylmore (1998). Esta abordagem não permite estabelecer os efeitos diretos e indiretos de uma variável independente com variáveis dependentes.…”
Section: Introductionunclassified
“…The beaker (containing the soil sample) was then placed in an oven at 105 ± 2 • C for 18 h. The natural water content method was used to calculate the SMHM. The SMHM can be used to estimate the soil available water-holding capacity (AWC) (Gupta and Larson, 1979) for the plant using the following equation: AWC = SWC − 2*SMHM, where SWC is the soil water content.…”
Section: Soil Maximum Hygroscopic Moisture (Smhm) and Soil Available mentioning
confidence: 99%
“…The soil tilled by the AS technique showed alternating changes in bulk density and alternately loosened strips of ridge and furrow. Previous studies demonstrated that the bulk density of the soil was closely related to the water storage capacity of the soil [17,18]. Subsoiling operations were carried out in the farmland ridge and furrow in the autumn of 2011 and early summer of 2012, respectively.…”
Section: Discussionmentioning
confidence: 99%